How to Develop the Korean Camping Culture and Industry: Focused on Camping Site Selection Attributes - Hyungchul Joo; Yoonso Choi (SAGE Open)
This study aims to promote camping as a healthy leisure culture rather than a passing trend. A literature review, expert interviews, and consultations were conducted to identify key factors influencing campers’ choice of campgrounds. The analytic hierarchy process (AHP) analysis was employed to determine the level of priority of these factors. The results showed that campers value facilities, operating hours, fees, and facility stability when selecting campgrounds. Facilities include camping grounds, shared facilities, and convenience amenities. Operating services encompass human services, reservation systems, and usage hours. Fees comprise price utility, charged services, and payment methods. Facility stability encompasses emergency response, firefighting facilities, and campground hygiene. The AHP analysis revealed that campers prioritize camping grounds and common facilities among facilities and campsite hygiene and firefighting facilities among facility stability. Human services, reservation systems, and reasonable fees were also found to be important. The findings highlight the need for effective facility management, safety measures, appropriate human services, and reasonable fees to encourage camping.